A boca do sapo - Paiva, Aline Gonçalves; Santos, Eliana Ferreira dos; Bernhardt, Cristiane Colossi; Quadros, Izabel Cristina Rezende de; Oliveira, Maria Auxiliadora de; Simião, Maria Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf